2015
DOI: 10.1159/000366443
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Endometriosis Fertility Index (EFI) for Predicting Spontaneous Pregnancy after Surgery: Further Considerations on Its Validity

Abstract: Background/Aims: The revised American Society for Reproductive Medicine classification of endometriosis has a limited predictive value for pregnancy after surgery. A tool for predicting spontaneous pregnancy or pregnancy following assisted reproduction technology (ART) represents a clinical need. This study aimed to (i) provide an external validation of the EFI score in predicting pregnancy in infertile Italian endometriosis women; (ii) evaluate the predictive value of EFI score on ART outcome for patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
3
16
0
2
Order By: Relevance
“…We demonstrated that the EFI scoring system could validly predict natural pregnancy after endometriosis surgery, which is in line with previous studies [13,17]. To our knowledge, this is the first report validating EFI for the prediction of natural conception after surgery in Korean women with endometriosis.…”
Section: Discussion/conclusionsupporting
confidence: 90%
See 2 more Smart Citations
“…We demonstrated that the EFI scoring system could validly predict natural pregnancy after endometriosis surgery, which is in line with previous studies [13,17]. To our knowledge, this is the first report validating EFI for the prediction of natural conception after surgery in Korean women with endometriosis.…”
Section: Discussion/conclusionsupporting
confidence: 90%
“…Patients with severe disease were encouraged to proceed directly to the ART center without attempting natural conception. Such patients were readily excluded, possibly contributing to "active censorship" similar to previous studies [13,17].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sa validation interne et externe permet aujourd'hui, à l'issue de la chirurgie, de proposer une prise en charge personnalisé e chez les patientes endomé -triosiques infertiles et opé ré es. Cinq é tudes montrent qu'il existe une association significative entre le score EFI et la probabilité de grossesse spontané e dans les 12 mois [52][53][54][55][56]. Dans la sé rie française portant sur 417 patientes opé ré es [53], les taux de grossesse spontané e ont é té de 42 % et 57 % lorsque le score é tait !…”
Section: L'endome´trioseunclassified
“…L'EFI est un outil nouveau et performant, permettant de guider la prise en charge postopé ratoire [52][53][54][55][56]. La prise en compte de la ré serve ovarienne permet d'obtenir un traitement individualisé pour chaque couple [53,118].…”
Section: Endome´trioseunclassified